PROGNOSTIC IMPACT OF COMMUNITY-ACQUIRED AND HOSPITAL-ACQUIRED HYPONATREMIA IN PATIENTS WITH DECOMPENSATED HEART FAILURE - D. Yu. Shchekochikhin; Ph. Yu. Kopylov; N. L. Kozlovskaya; A. L. Syrkin (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To compare prognostic impact of community-acquired and hospital-acquired hyponatremia in hospitalized patients with decompensated heart failure Material and methods. Data of 120 patients with decompensated heart failure were analyzed. Hyponatremia was defined as serum sodium concentration of 135 mmol/l or less. Several outcomes were analyzed: mortality, transfer to intensive care unit (ICU), resistance to loop diuretics and worsening renal function.Results. 13.0% of patients had community-acquired hyponatremia, 9.6% - hospital-acquired hyponatremia. Community-acquired hyponatremia was associated with increased mortality [odds ratio (OR)=7.8], admission to ICU (OR=19.1) and resistance to loop diuretics (OR=4.8). Hospital-acquired hyponatremia was associated with worsening renal function (OR=12.4).Conclusion. Both, community-acquired and hospital hyponatremia have negative impact in hospitalized patients with decompensated heart failure.